PHILOSOPHICAL CONCEPT OF MAN IN THE POEM "PARADISE LOST" - Парнус, Екатерина; Фурсова, Людмила; Свисюк, Елена (SWorldJournal, 2021)
Abstract. Empirical research is based on the John Milton’s poem "Paradise Lost". The role of a person who is at the center of the universe and independently chooses a way of life as well as a difficult way to find the truth is revealed. The paradigms of t